2020
DOI: 10.1088/1361-6579/ab9376
|View full text |Cite
|
Sign up to set email alerts
|

The effect of persistent U-shaped patterns in RR night-time series on the heart rate variability complexity in healthy humans

Abstract: Objective: U-shaped patterns, characteristic periods of time observed in tachograms, are a specific subgroup among very low frequency components characterized by relatively short periods of smooth accelerations followed by decelerations of heart rhythm. In this study, we characterize this phenomenon and its effect on heart rate variability (HRV) parameters. Approach: We calculated linear (the mean and standard deviation of RR intervals, RMSSD, pNN50 and the power of the frequency components) and nonlinear (V0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The persistent homology method has some similarities with the analysis of the statistics of so-called U-shape patterns (see [55,56] and references therein). U-shapes are parts of the tachogram in the night-time recordings consisting of relatively short periods of smooth accelerations followed by decelerations in the heart rhythm, lasting in total approximately 20-40 seconds.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The persistent homology method has some similarities with the analysis of the statistics of so-called U-shape patterns (see [55,56] and references therein). U-shapes are parts of the tachogram in the night-time recordings consisting of relatively short periods of smooth accelerations followed by decelerations in the heart rhythm, lasting in total approximately 20-40 seconds.…”
Section: Plos Onementioning
confidence: 99%
“…U-shapes are parts of the tachogram in the night-time recordings consisting of relatively short periods of smooth accelerations followed by decelerations in the heart rhythm, lasting in total approximately 20-40 seconds. So-called short acceleration-deceleration events [56] show some similarities with Ushape patterns but could not be classified as such due to their shorter duration, symmetric acceleration, or smaller relative amplitude. Persistent homology methods provide a more general approach in which each U-shape or short acceleration-deceleration event is related to a persisting connected component of the graph built from the RR data (a persistence interval).…”
Section: Plos Onementioning
confidence: 99%
“…Ultrasonography can be augmented with ultrasound shear wave elastography (SWE) that enable continuous measurement of viscoelastic properties of musculoskeletal tissues [166]. SWE can be used to study the muscle sti-ness after training session [830], Achilles tendon stiness in natural environments using a wearable SWE [302], Achilles tendon stiness and its eect on ROM in squat [270], dynamical muscle contraction during squat [571] with deep learning inversion [224], changes in viscoelastic properties of muscle during fatigue [119], and ecacy of stretch- [756,877]. From these measurements, heart rate variability (HRV) is the most commonly derived parameter [193,389], with the ring or wrist band monitor/sensor oering ease-of-…”
Section: Muscle Morphology and Its Viscoelastic Propertiesmentioning
confidence: 99%
“…U-shaped patterns were widely observed in healthy humans. Previous studies showed that these patterns have a considerable impact on the HRV parameters describing the VLF component, persistency, nonlinear correlations and multifractal properties, although their percentage contribution is small compared to the whole night-time series (on the average 3.1±1.7%) [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…They are, in a domain of RR time intervals, the most laminar structures in nightrime recordings. They are defined as accelerationdeceleration periods in RR interval series, with duration between 20-40 s, and amplitude at smaller at least than 85% of the mean RR interval [1,2].…”
Section: Introductionmentioning
confidence: 99%